An assessment of the clinical efficacy of Alflutop in the process of treating of patients with knee joint osteoarthrosis and a study of its effect on the articular cartilage by MRI data - Buryanov, Oleksandr; Dykan, Iryna; Mironiak, Lyudmyla; Riabikin, Olexiy; Kvasha, Volodymyr; Sobolevskiy, Yuriy; Omelchenko, Taras (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
The purpose of the present research was to improve results of treatment in patients with deforming arthrosis of the knee joint by means of Alflutop application. The analysis of the results which was carried out proved a high efficacy of this preparation for treating degenerative and dystrophic lesions of joints and showed an objective necessity of its wide application to practice.